(untitled) (Journal of Nepal Geological Society, 1998)
Satellite data are exploited to study the Butwal, Hetauda, Bagmati River and Trijuga sections of the Siwaliks and the results of the investigations are discussed. Remote Sensing data deliver information on lithological units, orientation of the strata (bedding as iron plates, strike directions) and tectonic structures (strong lines and other features) of the region. The data supplemented by multicolour satellite images are valuable assets in deciphering the geology of an area. The satellite LANDSAT-TM data of two false colour composites of the Bagmati and Trijuga River area of the Sub-Himalayan (Siwalik) region show interesting tonal and morphological (topographical and textural) differences. Such variations can be attributed to lithological discrepancies among the geological formations of the area. At least three different lithological units of the Siwaliks are recognised. They are fine, medium and coarse grained elastic deposits corresponding to the three fold divisions (Lower, Middle and Upper) of the Sub-Himalaya. The three lithological units are morphologically related to the smooth, rugged and dissected terrains. Shifting up of the Siwalik range near about I2 km northeast of Lahan, active fault alignment along with MBT (north of Gaighat), Bhabar Zone (southern part of the foothills of the Siwaliks), Dun Valley (Hetauda) are prominent features observed in the TM-scenes. Rivers originating in the middle mountains of Lesser Himalaya like Trijuga, Bagrnati, Rapti, Tinau and Banganga drain through the Siwaliks crossing the major structure MBT suggesting an antecedent river type. Other streams originating in the Siwaliks and flowing southward are obsequent and subsequent.